The Java tutorial : a short course on the basics - Gallardo, Raymond; Hommel, Scott; Kannan, Sowmya; Gordon, Joni; Zakhour, Sharon (Addison-Wesley, 2015)
The Java® Tutorial, 6th Edition, is based on the Java Platform, Standard Edition (Java SE) 8. This revised and updated edition introduces the new features added to the platform, including lambda expressions, default methods, aggregate operations, and more. An accessible and practical guide for programmers of any level, this book focuses on how to use the rich environment provided by Java to build applications, applets, and components. Expanded coverage includes a chapter on the Date-Time API and a new chapter on annotations, with sections on type annotations and pluggable type systems as well as repeating annotations. In addition, the updated sections "Security in Rich Internet Applications" and "Guidelines for Securing Rich Internet Applications" address key security topics. The latest deployment best practices are described in the chapter "Deployment in Depth." If you plan to take one of the Java SE 8 certification exams, this book can help. A special appendix, "Preparing for Java Programming Language Certification," details the items covered on the available exams. Check online for updates. All of the material has been thoroughly reviewed by members of Oracle Java engineering to ensure that the information is accurate and up to date. This book is based on the online tutorial hosted on Oracle Corporation's website at http://docs.oracle.com/javase/tutorial .